2016
DOI: 10.1080/03019233.2016.1264153
|View full text |Cite
|
Sign up to set email alerts
|

Sintering characteristics and kinetics of acidic haematite ore pellets with and without mill scale addition

Abstract: Haematite ore pellets require very high induration temperature (>1573 K) while, magnetite ore pellets require much lower temperature due to the oxidation of magnetite during induration. Mixing of some magnetite in haematite ore can improve the sintering property of pellets during induration. Mill scale is a waste material of steel plant which contains mainly FeO and Fe 3 O 4. It can also be blended in haematite ore pellet mix which can enhance diffusion bonding and recrystallisation bonding and facilitate sint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As compared to Iron Ore No.2 has a 53% of 44-micron excessive fineness makes the grains react more and, instead of transforming solid solution, liquid melt deteriorates the structure. As it can be noted from particle size analysis, more fineness in either iron ore always does not support the strength an optimal value makes the pellets strong [26,27]. The chemical composition of iron ore fines behaves differently as per the thermal treatment process of pelletization.…”
Section: Physical Properties (Cold Compression Strength (Ccs) and App...mentioning
confidence: 99%
“…As compared to Iron Ore No.2 has a 53% of 44-micron excessive fineness makes the grains react more and, instead of transforming solid solution, liquid melt deteriorates the structure. As it can be noted from particle size analysis, more fineness in either iron ore always does not support the strength an optimal value makes the pellets strong [26,27]. The chemical composition of iron ore fines behaves differently as per the thermal treatment process of pelletization.…”
Section: Physical Properties (Cold Compression Strength (Ccs) and App...mentioning
confidence: 99%
“…Reducibility of iron-bearing burden is dominant in the blast furnace. The large-scale utilization of high basicity sinter is based on its high reducibility and good softening performance [53]. Generally speaking, the reducibility of acid pellets is poor [54,55], while the reducibility of MgO-bearing pellets has been improved to a considerable extent [56][57][58].…”
Section: Reducibilitymentioning
confidence: 99%
“…However, the efficient utilization of iron-based solid wastes is not fully realized because of the high consumption of sintering materials and the low usage of them as secondary resources. Y. Rajshekar et al [21][22][23] found that the iron oxide scale can be used as an additive to hematite pellets to improve its metallurgical properties such as reduction index.…”
Section: Doi: 101002/srin202200084mentioning
confidence: 99%